Immune attributes of cardiac‐derived adherent proliferating (CAP) cells in cardiac therapy. (2nd March 2012) - Haag, Marion; Stolk, Meaghan; Ringe, Jochen; Linthout, Sophie Van; Tschöpe, Carsten; Sittinger, Michael; Seifert, Martina
Abstract Cardiac‐directed cell therapies show potential to reduce mortality and morbidity in heart disease. However, high functional efficacy should be complimented with low immunogenicity, in particular if allogeneic cell sources are applied. Therefore, we aimed to examine cardiac‐derived adherent proliferating (CAP) cells with respect to their immunogenicity and immune modulatory features in vitro. Human CAP cells were isolated from cardiac biopsies and screened in a CFSE‐based proliferation assay in co‐cultures with phytohaemagglutinin (PHA)‐stimulated human peripheral blood lymphocytes (PBMCs) or mixed lymphocyte cultures (MLCs) to assess their potential to induce immune cell proliferation or activation by flow cytometry. Moreover, levels of pro‐ and anti‐inflammatory cytokines in supernatants of co‐cultures were analysed. The capacity of CAP cells to induce the generation of regulatory T cells (Tregs) was determined by flow cytometric measurement of FoxP3 expression. CAP cells of different donors (n = 5) showed low immunogenicity in co‐cultures with human allogeneic PBMCs. In addition, they induced no change in the normal alloantigen‐driven immune responsiveness in MLCs. However, CAP cells significantly reduced the induction of immune cell proliferation in PBMCs cultures stimulated with the polyclonal trigger PHA. Adding CAP cells into MLCs or PHA‐stimulated cultures resulted in significantly reduced levels of TNFα or IFNγ, respectively, compared to controls without CAP cells. At early time points (day 2), interaction of CAP cells with PBMCs resulted in elevated proportions of FoxP3+CD4+CD25high+ cells. The results indicate that CAP cells have low immunogenicity and could be advantageous in cardiac repair by reducing inflammatory cytokines and inducing regulatory T cells. Copyright © 2012 John Wiley & Sons, Ltd.